Les Allemands à l’Exposition universelle de Paris en 1900 ou l’expérience d’un patriotisme mal compris - Philippe Alexandre (Recherches Germaniques)
At a time when the relationships were temporarily serene, the 1900 World Fair was in many regards an opportunity both for German and French people for an exceptional encounter. This event could actually be said to have been a mass movement, either in terms of people moving, ideas, or productions in all areas of human activity. The Exhibition was a place of intense cultural exchange, fierce rivalry and competition and hectic dynamism made even more so by national newspapers and magazines of the time. The reports put across the notion of a subtle interplay of mirror-like glances and effects. The idea was to convey a forceful national image to the neighbouring country and its people, among others, and to assert the nation’s cultural and economic leadership. The spread of knowledge was favoured by millions of visitors, among whom delegates sent by local communities, experts, observers, newspapermen and journalists. Yet official publications also played a major part as they were to convey a convincing image of their own countries aimed at the public and prospective customers or possible partners, thus opening inroads for new economic prospects. As 130 international meetings were set up and held with a more or less direct connection with the Exhibition, the exchange of knowledge between nations, the development of cooperation and technology transfer were undoubtedly encouraged. Yet it cannot be ignored that these exchanges between Germany and France were severely disrupted by the misplaced feeling of patriotism or national chauvinism. In this respect part of the blame was to be laid on the media.